Latex blends of amorphous perfluorinated polymers and articles derived therefrom - Patents.com
Patent Information
- Application Number
- JP2021535517
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-12-20
- Filing Date
- 2019-12-19
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2039-12-19
Smart Images

Figure 0007645800000001 
Figure 0007645800000002 
Figure 0007645800000003
Abstract
Description
[Technical field]
[0001] Latex blends are disclosed that include an amorphous perfluoropolymer and an aqueous dispersion of modified polytetrafluoroethylene (PTFE). Such blends can be used to produce filled perfluorinated elastomers that can have improved plasma resistance and / or temperature stability. Summary of the Invention
[0002] It would be desirable to identify filled perfluorinated elastomeric compositions that have improved properties, such as heat resistance and / or plasma resistance.
[0003] In one embodiment, a latex blend is disclosed, comprising an amorphous perfluoropolymer latex and an aqueous dispersion of semi-crystalline fluoropolymer particles, wherein the semi-crystalline fluoropolymer particles comprise a tetrafluoroethylene copolymer containing 1 wt.% or less of at least one additional fluorinated monomer, and the semi-crystalline fluoropolymer particles (i) have a melt flow index (at 372°C, 2.16 kg) of less than 50 g / 10 min, or (ii) are not melt processable and have a standard specific gravity of less than 2.200, and the semi-crystalline fluoropolymer particles have an average diameter of more than 100 nm.
[0004] In one embodiment, a curable perfluoropolymer composition is disclosed that comprises a homogeneous blend of amorphous perfluoropolymer particles and semi-crystalline fluoropolymer particles, the semi-crystalline fluoropolymer particles comprising a tetrafluoroethylene copolymer containing 1 wt.% or less of at least one additional fluorinated monomer, the semi-crystalline fluoropolymer particles (a) have a melt flow index (at 372°C, 2.16 kg) of less than 50 g / 10 min, or (b) are not melt processable and have a standard specific gravity of less than 2.200, and the semi-crystalline fluoropolymer particles have an average diameter of more than 100 nm.
[0005] In another aspect, a cured perfluorinated elastomer is disclosed comprising a perfluoropolymer filled with semi-crystalline fluoropolymer particles, the semi-crystalline fluoropolymer particles comprising a tetrafluoroethylene copolymer containing 1 wt. % or less of at least one additional fluorinated monomer, the semi-crystalline fluoropolymer particles either (a) have a melt flow index (at 372° C., 2.16 kg) of less than 50 g / 10 min, or (b) are not melt processable and have a standard specific gravity of less than 2.200, and the semi-crystalline fluoropolymer particles have an average diameter of more than 100 nm.
[0006] The above summary of the disclosure is not intended to describe every embodiment. The details of one or more embodiments of the invention are set forth in the following description. Other features, objects, and advantages will be apparent from the description and from the claims. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] As used herein, The terms "a," "an," and "the" are used interchangeably and mean one or more; The term "and / or" is used to indicate that either or both of the stated things may occur. For example, A and / or B includes (A and B) as well as (A or B); "Backbone" refers to the main continuous chain of a polymer. "Crosslinking" refers to the joining of two preformed polymer chains using a chemical bond or chemical group. "Cure site" refers to a functional group that may participate in crosslinking. "Copolymerization" refers to the polymerization of monomers together to form a polymer backbone. A "monomer" is a molecule that can undergo polymerization and subsequently form part of the basic structure of a polymer; and "Polymer" refers to a macrostructure containing repeating copolymerized monomer units.
[0008] Further herein, the recitation of ranges by endpoints includes all numbers subsumed within that range (eg, 1 to 10 includes 1.4, 1.9, 2.33, 5.75, 9.98, etc.).
[0009] Further, as used herein, the term "at least one" includes all numbers greater than or equal to 1 (e.g., at least 2, at least 4, at least 6, at least 8, at least 10, at least 25, at least 50, at least 100, etc.).
[0010] As used herein, "comprising at least one of A, B, and C" refers to a single element A, a single element B, a single element C, A and B, A and C, B and C, and combinations of all three.
[0011] This application relates to amorphous perfluorinated polymers used in the manufacture of perfluorinated elastomers. Perfluorinated elastomers are used in a wide range of applications that encounter harsh environments, especially end uses exposed to high temperatures and aggressive chemicals. In the semiconductor industry, perfluorinated elastomers are used in processes that require resistance to NF3 plasma. However, this industry has stringent requirements for material purity, especially with regard to metal ions.
[0012] High fluorine-containing polymers can be used as fillers to provide base polymers with improved performance (thermal stability, plasma resistance, etc.). PTFE and PFA polymers are both high fluorine content polymers. Traditionally, PFA (perfluoroalkoxy copolymer) polymers have been used as fillers in fully fluorinated elastomer articles for semiconductor applications because PFA is a melt-processable thermoplastic and easy to process. The incorporation of PTFE (TFE homopolymer) would be ideal to add to amorphous perfluoropolymers, but PTFE has a tendency to fibrillate unmodified PTFE, resulting in a rough appearance in the final product, due to its excellent thermal and chemical stability, as shown in the examples section.
[0013] The modified PTFE is a tetrafluoroethylene (TFE) copolymer with a low amount of comonomer. The present disclosure relates to a latex blend comprising an amorphous perfluorinated polymer and an aqueous dispersion of semi-crystalline fluoropolymer particles of a TFE copolymer with a low concentration of comonomer.
[0014] Semi-crystalline fluoropolymer particles
[0015] The particles of the present disclosure are semi-crystalline fluoropolymer particles of TFE copolymer.The TFE copolymer disclosed herein is a polymer of TFE modified with a small amount, for example, 1, 0.5, 0.1, 0.05, or even 0.01% by weight, of at least one additional fluorinated monomer that is not TFE.Exemplary additional fluorinated monomers include those of the formula: R f -O-(CF2) m CF=CF2 wherein m is 0 or 1 and Rf represents a perfluoroalkyl residue containing at least one carbon atom optionally interrupted by at least one linking (i.e., in-chain) oxygen atom. Exemplary unsaturated fluorinated ether monomers include perfluoro(2-propoxypropyl vinyl) ether (PPVE-2), perfluoro(methyl vinyl) ether (PMVE), perfluoro(ethyl vinyl) ether (PEVE), perfluoro(3-methoxy-n-propyl vinyl) ether (MV-31), perfluoro(2-methoxy-ethyl vinyl) ether, perfluoro(n-propyl vinyl) ether (PPVE-1), perfluoro(methyl allyl) ether (MA-1), perfluoro(ethyl allyl) ether (MA-2), perfluoro(n-propyl allyl) ether (MA-3), perfluoro(n-butyl allyl) ether (MA-4), CF3-O-(CF2)3-O-CF2-CF=CF2 (MA31), and F3C-(CF2)2-O-CF(CF3)-CF2-O-CF(CF3)-CF2-O-CF=CF2 (PPVE-3).
[0016] In one embodiment, the TFE copolymer is modified with perfluorinated vinyl ether or perfluorinated allyl ether to achieve low deformation under load. In one embodiment, the TFE copolymer is modified with a small amount of perfluorinated allyl ether monomer. In one embodiment, the semi-crystalline fluoropolymer particles contain groups, such as nitrile, bromine, and / or iodine sites, that can interact (e.g., bond interaction) with the amorphous perfluoropolymer particles. Such groups may be introduced into the semi-crystalline fluoropolymer via chain transfer agents or cure site monomers used during polymerization.
[0017] In one embodiment, the semi-crystalline fluoropolymer particles are random copolymers made by copolymerizing tetrafluoroethylene with different fluorinated monomers, such as perfluorinated allyl ethers or vinyl ethers.
[0018] In another embodiment, the semicrystalline fluoropolymer particles are core-shell particles that include a core of one composition (such as a TFE homopolymer or TFE copolymer) and a shell of a different composition (e.g., shell derived from a different monomer, or a monomer at a different concentration than the core). For core-shell particles, typically the core has an average diameter of 10, 25, or even 40 nm or more and up to 100, 125, or even 150 nm. The shell can be thick or thin. For example, in one embodiment, the outer shell is a TFE copolymer with a thickness of 100, or even 125 nm or more and up to 200 nm. In another embodiment, the outer shell is a TFE copolymer with a thickness of 1, 2, or even 5 nm or more and up to 15, or even 20 nm. Exemplary modified PTFE core-shell particles have a shell derived from perfluorinated vinyl ether, perfluorinated allyl ether, and / or cure site-containing monomer. The total content of modifiers (e.g., perfluorinated vinyl ethers, perfluorinated allyl ethers, and cure site monomers) is 1, 0.5, or even 0.2% by weight on average of the weight of the particle. In one embodiment, the content of the second monomer in the semicrystalline fluoropolymer particles is about parts per thousand.
[0019] The semi-crystalline fluoropolymers described above can be prepared using techniques known in the art, for example, by aqueous emulsion polymerization with or without a fluorinated emulsifier, followed by coagulation, flocculation and drying of the latex to recover the semi-crystalline fluoropolymer.
[0020] The semi-crystalline fluoropolymer disclosed herein is a particle.In one embodiment, the average primary particle size of particles in latex is 50, 75, 100, or even 125 nm or more and up to 200, 250, 300, 400, or even 500 nm.These primary particles can be aggregated to form aggregates with an average diameter of 50, 75, 100, or even 125 micrometers or more and up to 500, 600, 800, or even 1000 micrometers.
[0021] The semi-crystalline fluoropolymer particles may or may not be melt processable.
[0022] Melt-processable semi-crystalline fluoropolymer particles are materials with low molecular weight. Such low molecular weight polymers have a MFI (melt flow index) of less than 50, 45g / 10min, or even 40g / 10min at 372°C and 2.16kg load. Exemplary melt-processable semi-crystalline fluoropolymer particles include core-shell particles derived from fluorinated vinyl ether (e.g., PPVE, PMVE) or fluorinated allyl ether as modifier in shell and / or core.
[0023] Semicrystalline fluoropolymer particles with higher molecular weight fluoropolymers are essentially non-melt processable (having a melt flow index of less than 0.1, 0.05 g / 10 min, or even less than 0.001 g / 10 min at 372° C. and 21.6 kg). The molecular weight of these non-melt processable polymers cannot be measured by conventional techniques. Therefore, indirect methods that correlate with molecular weight, such as standard specific gravity (SSG), are used. The lower the SSG value, the higher the average molecular weight. The SSG of the non-melt processable semicrystalline fluoropolymers of the present disclosure can be up to 2.200, 2.190, 2.185, 2.180, 2.170, 2.160, 2.157, 2.150, 2.145, or even 2.130 g / cm, as measured according to ASTM D4895-04. 3 Exemplary non-melt processable semi-crystalline fluoropolymer particles include core-shell particles derived from vinyl ethers or allyl ethers, such as PPVE, PMVE, as modifiers in the shell and / or core, and random copolymer particles derived from nitrile-containing cure site monomers.
[0024] In one embodiment, the semi-crystalline fluoropolymer particles have a melting point of 310, 320° C., or even 330° C. or greater, which can be determined by analyzing the coagulated and dried fluoropolymer.
[0025] Amorphous Perfluoropolymer
[0026] Amorphous perfluoropolymers are macromolecules that contain repeating copolymerized divalent monomer units, each of which is perfluorinated (in other words, the monomer unit contains at least one C-F bond and no C-H bonds). Amorphous perfluoropolymers may contain non-perfluorinated end groups based on initiators and / or chain transfer agents used as known in the art.
[0027] Amorphous perfluoropolymers are generally obtained by polymerizing one or more perfluorinated monomers, such as perfluorinated olefins and perfluorinated olefins that contain ether bonds. Exemplary perfluorinated monomers include tetrafluoroethylene, hexafluoropropylene, pentafluoropropylene, trifluorochloroethylene, perfluoro-vinyl ether monomers, and perfluoroallyl ether monomers.
[0028] Examples of perfluoroether monomers that may be used in the present disclosure include those of the formula CF2=CF(CF2) m -OR f (In the formula, m is 0 or 1, and R f represents a perfluorinated aliphatic group which may contain zero, one or more oxygen atoms and up to 12, 10, 8, 6, or even 4 carbon atoms.
[0029] Examples of perfluorovinyl ether monomers are represented by the formula CF2 = CFO(R a f O) n (R b f O) m R c f [In the formula, R a f and R b f are different linear or branched perfluoroalkylene groups having 1 to 6 carbon atoms, particularly 2 to 6 carbon atoms; m and n are independently 0 to 10; R c fis a perfluoroalkyl group having 1 to 6 carbon atoms. Specific examples of perfluorinated vinyl ethers include perfluoro(methyl vinyl) ether (PMVE), perfluoro(ethyl vinyl) ether (PEVE), perfluoro(n-propyl vinyl) ether (PPVE-1), perfluoro-2-propoxypropyl vinyl ether (PPVE-2), perfluoro-3-methoxy-n-propyl vinyl ether, perfluoro-2-methoxy-ethyl vinyl ether, and [ka] Examples include:
[0030] Examples of perfluoroallyl ether monomers that may be used in the present disclosure include those of the formula CF2=CF(CF2)-OR f [In the formula, R f represents a perfluorinated aliphatic group which may contain zero, one or more oxygen atoms and up to 10, up to 8, up to 6, or even up to 4 carbon atoms. Specific examples of perfluorinated allyl ethers include those equivalent to CF2=CF-CF2-O-(CF2) n F [wherein n is an integer of 1 to 5], and CF2=CF-CF2-O-(CF2) x -O-(CF2) y -F [wherein x is an integer of 2 to 5, and y is an integer of 1 to 5.] Specific examples of perfluorinated allyl ethers include perfluoro(methylallyl) ether (CF2=CF-CF2-O-CF3), perfluoro(ethylallyl) ether, perfluoro(n-propylallyl) ether, perfluoro-2-propoxypropyl allyl ether, perfluoro-3-methoxy-n-propyl allyl ether, perfluoro-2-methoxy-ethyl allyl ether, perfluoro-methoxy-methyl allyl ether, and [ka] and combinations thereof.
[0031] In the present disclosure, the perfluorinated polymer may be polymerized in the presence of a chain transfer agent and / or cure site monomer to introduce cure sites such as I, Br, and / or CN into the fluoropolymer.
[0032] Exemplary chain transfer agents include iodo chain transfer agents, bromo chain transfer agents, or chloro chain transfer agents. For example, suitable iodo chain transfer agents for polymerization include those of the formula RI x [wherein (i) R is a perfluoroalkyl group or a chloroperfluoroalkyl group having 3 to 12 carbon atoms, and (ii) x=1 or 2]. The iodo chain transfer agent is I(CF2) n -O-(CF2) m The perfluorinated iodo compounds may be perfluorinated iodo compounds such as -I, where n and m are integers independently selected from 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, or even 12. Exemplary iodo-perfluorinated compounds include 1,3-diiodoperfluoropropane, 1,4-diiodoperfluorobutane, 1,6-diiodoperfluorohexane, 1,8-diiodoperfluorooctane, 1,10-diiodoperfluorodecane, 1,12-diiodoperfluorododecane, 2-iodo-1,2-dichloro-1,1,2-trifluoroethane, 4-iodo-1,2,4-trichloroperfluorobutane, and mixtures thereof. In some embodiments, bromine is represented by the formula RBr x The chain transfer agent is derived from a brominated chain transfer agent of the formula: (i) R is a perfluoroalkyl group or a chloroperfluoroalkyl group having 3 to 12 carbon atoms, and (ii) x is 1 or 2. The chain transfer agent may be a perfluorinated bromo compound.
[0033] In one embodiment, the cure site has the formula: (a) CX2=CX(Z), where (i) each X is independently H or F, and (ii) Z is I, Br, R f -U, where U is I or Br, and R f is a perfluorinated alkylene group optionally containing an O atom; or (b) Y(CF2) qY, wherein (i) Y is Br, I, or Cl, and (ii) q is 1 to 6. In addition, non-fluorinated bromo or iodo olefins, such as vinyl iodides and allyl iodides, can be used. In some embodiments, the cure site monomer is derived from one or more compounds selected from the group consisting of CF2=CFCF2I, ICF2CF2CF2I, CF2=CFCF2CF2I, CF2=CFOCF2CF2I, CF2=CFOCF2CF2CF2I, CF2=CFOCF2CF2CH2I, CF2=CFCF2OCH2CH2I, CF2=CFO(CF2)3-OCF2CF2I, CF2=CFCF2Br, CF2=CFOCF2CF2Br, CF2=CFCl, CF2=CFCF2Cl, and combinations thereof.
[0034] In another embodiment, the cure site monomer comprises a nitrogen-containing cure moiety. Useful nitrogen-containing cure site monomers include nitrile-containing fluorinated olefins and nitrile-containing fluorinated vinyl ethers [perfluoro(8-cyano-5-methyl-3,6-dioxa-1-octene), CF2=CFO(CF2) L CN (wherein L is an integer from 2 to 12), CF2=CFO(CF2) u OCF(CF3)CN (wherein u is an integer from 2 to 6), CF2=CFO[CF2CF(CF3)O] q (CF2O) y CF(CF3)CN or CF2=CFO[CF2CF(CF3)O] q (CF2) y OCF(CF3)CN (wherein q is an integer from 0 to 4, and y is an integer from 0 to 6), or CF2=CF[OCF2CF(CF3)] r O(CF2) tCN, where r is 1 or 2 and t is an integer from 1 to 4, as well as derivatives and combinations of the above. Examples of nitrile-containing cure site monomers include CF2=CFO(CF2)5CN, CF2=CFOCF2CF(CF3)OCF2CF2CN, CF2=CFOCF2CF(CF3)OCF2CF(CF3)CN, CF2=CFOCF2CF2CF2OCF(CF3)CN, CF2=CFOCF2CF(CF3)OCF2CF2CN, and combinations thereof.
[0035] In one embodiment, the amorphous perfluoropolymer contains Br and / or I cure sites and is substantially free of nitrile cure sites, meaning that it contains less than 0.5, 0.1 wt.%, or even less than 0.01 wt.%, or even no detectable levels of nitrile cure sites, based on the total weight of the amorphous perfluoropolymer.
[0036] The amorphous perfluoropolymer is a latex comprising a plurality of amorphous perfluoropolymer particles in an aqueous continuous phase. In one embodiment, the amorphous perfluoropolymer particles have an average particle size of 50, 60, 70, 80 nm, or even 90 nm or more and up to 120, 140, 150, 16, 18 nm, or even 200 nm.
[0037] blend
[0038] The latex blends disclosed herein comprise an aqueous dispersion of an amorphous perfluoropolymer blended with an aqueous dispersion of semi-crystalline fluoropolymer particles.
[0039] Typically, the aqueous dispersion of semi-crystalline fluoropolymer particles has a solids content of 10, 15, or even 20% by weight or more and up to 30, 35, or even 40% by weight.
[0040] Typically, the aqueous dispersion of amorphous perfluoropolymer has a solids content of 10, 15, 20, or even 25% by weight or more.
[0041] The two aqueous dispersions are contacted with each other and then blended using techniques known in the art, such as low shear to prevent coagulation. In one embodiment, the latex blend comprises 5, 10, 15, 20, or even 25% by weight or more and 30, 40, or even 50% by weight or less of semi-crystalline fluoropolymer particles per amorphous perfluoropolymer.
[0042] In one embodiment, the latex blend has a total solids content of 10, 15, 20, 25, 30, or even 40 weight percent or greater.
[0043] After the dispersions are homogeneously blended, the latex blend can be coagulated using conventional physical and chemical methods. In physical methods, the dispersion is subjected to strong (high) shear using an agitator, which can coagulate the particles (typically by a rotor stator with a shear rate of more than 1000 (1 / sec)). Another method of physical coagulation is the freeze-thaw method. The dispersion is cooled sufficiently to freeze, destabilizing the dispersion so that the coagulated liquid separates from the liquid upon thawing. In general, this technique is not favorable for scale-up due to its scalability and intensive energy requirements. In chemical coagulation, electrolytes or inorganic salts are added to the dispersion to reduce its stability, thereby causing coagulation.
[0044] In one embodiment, it may be preferred to use a chemical coagulation method in which an electrolyte or inorganic salt is added to the polymer dispersion. Examples of electrolytes used to chemically coagulate the fluoropolymer primary particles include HCL, H2SO4, HNO3, H3PO4, Na2SO4, MgCl2, Al2(SO4)3, and ammonium carbonate. Among these compounds, it is preferred to use compounds that can volatilize during the drying process of the coagulate. Examples of inorganic salts used to chemically coagulate the fluoropolymer primary particles include alkali metal salts, alkaline earth metal salts of nitric acid, hydrohalic acid, phosphoric acid, and sulfuric acid, as well as ammonium salts, molybdate salts, sodium phosphate monobasic or dibasic, ammonium bromide, potassium chloride, calcium chloride, copper chloride, and calcium nitrate. These electrolytes and inorganic salts can be used individually or in combination of two or more. In one preferred embodiment, an acid such as HNO3 is used to coagulate the latex blend.
[0045] After solidification, the collected solid (referred to herein as agglomerated fluoropolymer blend containing semicrystalline fluoropolymer particles and amorphous perfluoropolymer) can be rinsed, dried (e.g., at a temperature of 90°C or higher), and processed using techniques known in the art. For example, the blend of amorphous perfluoropolymer with semicrystalline fluoropolymer particles can be kneaded using standard mixing equipment for dry blend components. Mixing methods include, for example, kneading using a rubber two-roll, pressure kneader, or Banbury mixer. As used herein, dry blending refers to blending components that contain little water or solvent, as opposed to latex, liquid dispersion, or solution blends in which significant amounts of water or solvent are present. Optionally, fillers and / or curing catalysts can be added.
[0046] Ideally, the semi-crystalline fluoropolymer particles should have good compatibility with the amorphous perfluoropolymer latex to enable a filled perfluorinated elastomeric composition with good aesthetics (e.g., smooth and / or non-fibrillating products).
[0047] In one embodiment, the addition of an aqueous dispersion of semi-crystalline fluoropolymer particles to an amorphous perfluoropolymer latex results in an agglomerated fluoropolymer blend having a melting point that is at least 1.5, 2.0, 2.5, 3.0, 4.0, 5.0, 6.0, 8.0, or even 10.0° C. lower than the melting point of the semi-crystalline fluoropolymer particles themselves. In one embodiment, the agglomerated fluoropolymer blend has a melting point of at least 310, 320, 322, 324, or even 326° C. In one embodiment, the agglomerated fluoropolymer blend has a melting point of up to 325, 326, 327, 328, or even 329° C.
[0048] The stability of the composition can be determined by analyzing the agglomerated fluoropolymer blend using thermogravimetric analysis, which measures weight versus temperature. The derivative of this curve is then used to determine the temperature at which the inflection occurs. The inflection temperature can be interpreted as the onset temperature of decomposition of the semicrystalline fluoropolymer. In one embodiment, the agglomerated fluoropolymer blend has an inflection temperature of 500, 501, 502, 503, 504, or even 505°C or higher. In one embodiment, the agglomerated fluoropolymer blend has an inflection temperature of up to 510, 509, 508, 507, or even 506°C. TGA analysis can also be used to determine the amount of semicrystalline fluoropolymer particles in the agglomerated fluoropolymer blend, as described in the Examples section below. In one embodiment, the agglomerated fluoropolymer blend comprises 10, 12, 15, or even 18% by weight or more and up to 20, 22, 24, 26, 28, or even 30% by weight of semicrystalline fluoropolymer.
[0049] In one embodiment, at a frequency of 0.1 Hertz and 100° C., the coagulated fluoropolymer blend has a modulus of less than 450, 440, 420, 410 KPa, or even less than 405 KPa, as described in the Examples section.
[0050] In one embodiment, the coagulated fluoropolymer blend has a ML of less than 2.9, 2.8, or even 2.7 dNm, as described in the Examples section.
[0051] The recrystallization temperature refers to the temperature at which a semi-crystalline polymer in an amorphous state crystallizes when cooled. Depending on the number of crystal forms, a polymer may have one or more recrystallization points. In one embodiment, the agglomerated fluoropolymer blend has at least one recrystallization temperature less than 310, 309, 308, 307, or even 305°C.
[0052] In one embodiment, the agglomerated fluoropolymer blend comprises greater than or equal to 5, 10, or even 15 wt.% and up to 20, 25, 30, or even 35 wt.% semi-crystalline fluoropolymer.
[0053] A curative may be blended with the coagulated fluoropolymer blend to crosslink the amorphous perfluoropolymer and produce a filled perfluorinated elastomer.
[0054] Generally, an effective amount of curing agent in the curable composition, which may include two or more curing agents, is 0.1, 0.5, or even 1 wt. % or more and less than 10, 8, 6, or even 5 wt. %, although greater and lesser amounts of curing agent can be used.
[0055] The curing agent may include a curing agent and a curing catalyst. The curing agent may include those known in the art, including peroxides, triazine-forming curing agents, benzimidazole-forming curing agents, benzoxazole-forming curing agents, adipates, and acetates, among others. These curing agents may be used by themselves or in combination with another curing agent.
[0056] Peroxides may also be utilized as curing agents. Suitable organic peroxides are those which generate free radicals at the curing temperature. Dialkyl peroxides or bis(dialkyl peroxides) which decompose at temperatures above 50° C. are particularly preferred. In many cases, it is preferred to use di-tert-butyl peroxide, which has a tertiary carbon atom attached to the peroxy oxygen. The peroxides selected include benzoyl peroxide, dicumyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di-tert-butylperoxyhexane, 2,4-dichlorobenzoyl peroxide, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylchlorohexane, tert-butylperoxyisopropyl carbonate (TBIC), tert-butylperoxy 2-ethylhexyl carbonate (TBEC), tert-amylperoxide ... Peroxy 2-ethylhexyl carbonate, tert-hexylperoxyisopropyl carbonate, carbonoperoxy acid, O,O'-1,3-propanediyl OO,OO'-bis(1,1-dimethylethyl) ester, tert-butylperoxybenzoate, t-hexylperoxy-2-ethylhexanoate, t-butylperoxy-2-ethylhexanoate, di(4-methylbenzoyl) peroxide, lauryl peroxide, and cyclohexanone peroxide. Other suitable peroxide curing agents are listed in U.S. Patent No. 5,225,504 (Tatsu et al.). The amount of peroxide curing agent used is generally 0.1 to 5 parts by weight, preferably 1 to 3 parts by weight, per 100 parts of amorphous perfluoropolymer.
[0057] In one embodiment, the curing agent may be selected from triazine-forming curing networks. Such curing agents include organotin compounds (such as propargyl-, triphenyl- and allenyl-, tetraalkyl-, and tertaryltin curing agents); ammonia-generating compounds (see, for example, U.S. Pat. No. 6,281,296; ammonium salts such as perfluorooctanoates (see, for example, U.S. Pat. No. 5,565,512), and amidines (see, for example, U.S. Pat. No. 6,846,880), imidates (see, for example, U.S. Pat. No. 6,657,013), methamine complexes (see, for example, U.S. Pat. No. 6,657,012), and hydrochlorides (see, for example, U.S. Pat. No. 6,794,457).
[0058] In another embodiment, the fluoropolymer blend can be cured using one or more peroxide curatives along with an ammonia generating catalyst. The curing catalyst can, for example, include a first component and a second component, the first component being R'C(CF2R)O - Q + (In the formula, Q + is a non-interfering organic phosphonium, organosulfonium, or organoammonium cation, each R independently represents H, a halogen, a hydrocarbyl group, or a halogenated hydrocarbyl group, at least one carbon atom of the hydrocarbyl group may be further substituted with one or more heteroatoms selected from N, O, and S, R' represents H, a hydrocarbyl group, or a halogenated hydrocarbyl group, at least one carbon atom of the hydrocarbyl group may be further substituted with one or more heteroatoms selected from N, O, and S, or any two of R or R' together may form a divalent hydrocarbylene group, at least one carbon atom of the hydrocarbylene group may be further substituted with one or more heteroatoms selected from N, O, and S), and the second component is represented by [N≡CCFR''] bZ, where each R″ independently represents F or CF3, b represents any positive integer, and Z represents a b-valent organic moiety that does not contain interfering groups. See, for example, U.S. Pat. No. 7,294,677. Examples include the reaction product of CF3OCF2CF2CN with tetrabutylphosphonium 2-(p-toluyl)-1,1,1,3,3,3-hexafluoroisopropoxide; the reaction product of CF3OCF2CF2CN with tetrabutylammonium 2-(p-toluyl)-1,1,1,3,3,3-hexafluoroisopropoxide, and combinations thereof.
[0059] Curing can be effected using a catalyst that includes one or more ammonia-generating compounds. Ammonia-generating compounds include compounds that are solid or liquid at ambient conditions, but generate ammonia under curing conditions. Examples of such compounds include, for example, hexamethylenetetramine (urotropine), dicyandiamide, and compounds of formula A w+ (NH3) v Y w- (In the formula, A w+ Cu 2+ , Co 2+ , Co 3+ , Cu + Ni 2+ where w is equal to the valence of the metal cation, and Y w- is a counter ion, typically a halide, sulfate, nitrate, or acetate, and v is an integer from 1 to about 7).
[0060] Also useful as ammonia generating compounds are compounds of the formula [ka] where R is a hydrogen atom, or a substituted or unsubstituted alkyl, aryl, or aralkyl group having from 1 to about 20 carbon atoms. Particular useful triazine derivatives include hexahydro-1,2,5-s-triazine and acetaldehyde ammonia trimer.
[0061] In one embodiment, the curing agent is selected from the group consisting of those disclosed in U.S. Pat. No. 6,114,452 and the like. [ka] where A is selected from SO2, O, CO, alkyl of 1 to 6 carbon atoms, perfluoroalkyl of 1 to 10 carbon atoms, or a carbon-carbon bond connecting two aromatic rings. For example, useful curing agents include bis(aminophenols) such as 2,2-bis[3-amino-4-hydroxyphenyl]hexafluoropropane; bis(aminothiophenols) such as 4,4'-sulfonylbis(2-aminophenol), and tetraamines such as 3,3'diaminobenzidine, and 3,3',4,4'-tetraaminobenzophenone.
[0062] Bisamide zone compounds, such as 2,2-bis(4-carboxyphenyl)hexafluoropropane bisamidrazone, and bisamidrazones and bisamidoximes, may also be used as curing agents.
[0063] In another embodiment, the compound of formula {R(A) n} (-n) {QR' k (+)} n (Wherein, R is C1 to C 20 Alkyl or alkenyl, C3-C 20 Cycloalkyl or cycloalkenyl, or C6-C 20 A curing agent (or precursor thereof) may be used that is an aryl or aralkyl, which may be non-fluorinated, partially fluorinated, or fully fluorinated or hydrogen. R may contain at least one heteroatom, i.e., a non-carbon atom such as O, P, S, or N. R may also be used when one or more of the hydrogen atoms in the group is not Cl, Br, or I.{R(A) n} (-n)is an acid anion or an acid derivative anion, and n is the number of groups in the anion. A is an acid anion or an acid derivative anion, for example, A is a COO anion, SO3 anion, SO2 anion, SO2NH anion, PO3 anion, CH2OPO3 anion, (CH2O)2PO2 anion, C6H4O anion, OSO3 anion, O anion (when R is hydrogen, aryl, or alkylaryl), [ka] Anion, [ka] anion, and [ka] It can be an anion. R' is defined as R (above), the specific selection of R' can be the same as or different from the R bound to A, and one or more A groups can be bound to R. Q is phosphorus, sulfur, nitrogen, arsenic, or antimony, and k is the valence of Q. Q is nitrogen, the only fluoropolymer in the composition consists essentially of a terpolymer of tetrafluoroethylene, perfluorovinyl ether, and perfluorovinyl ether cure site monomers containing nitrile groups, not all R' are H, and k is one greater than the valence of Q (see, for example, U.S. Pat. Nos. 6,890,995 and 6,844,388). Examples include bistetrabutylphosphonium perfluoroadipate, tetrabutylphosphonium acetate, and tetrabutylphosphonium benzoate.
[0064] Other curing agents include bis-aminophenols (see, e.g., U.S. Pat. Nos. 5,767,204 and 5,700,879); organometallic compounds (see, e.g., U.S. Pat. No. 4,281,092); bis-amidoximes (see, e.g., U.S. Pat. No. 5,621,145); aromatic amino compounds; bisamidrazones; bisamidoximes; and tetraphenyltin.
[0065] Depending on the cure site components present, it is also possible to use dual cure systems, for example a perfluorinated polymer having copolymerized units of a nitrile-containing cure site monomer can be cured using a curing agent that includes a mixture of an organotin curing agent and a peroxide in combination with a coagent.
[0066] The co-agent (sometimes called co-curing agent) may be comprised of a polyunsaturated compound capable of working in conjunction with the peroxide to provide a useful cure. The co-agent may be one or more of the following compounds: triallyl cyanurate, triallyl isocyanurate, tri(methylallyl)isocyanurate, tris(diallylamine)-s-triazine, triallyl phosphate, N,N-diallyl acrylamide, hexaallyl phosphoramide, N,N,N',N'-tetraallyl malonamide, trivinyl isocyanurate, 2,4,6-trivinylmethyltrisiloxane, and tri(5-norbornene-2-methylene) cyanurate.
[0067] Other useful coagents include bis-olefins (see, for example, EP 0661304(A1), EP 0784064, and EP 0769521).
[0068] The fluoropolymer blend mixture (including the coagulated fluoropolymer blend, the cure system, and any additives) can then be processed and shaped, such as by extrusion or molding, to form articles of various shapes, such as sheets, hoses, hose linings, O-rings, gaskets, or seals, composed of the compositions of the present disclosure. The shaped article can then be heated to cure the perfluoropolymer rubber composition and form a cured elastomeric article.
[0069] Pressing of the kneaded mixture (i.e., press curing) is typically carried out at a temperature of about 120°C to 220°C, preferably about 140°C to 200°C, for about 1 minute to about 15 hours, usually about 1 to 15 minutes. A pressure of about 700 kPa to 20,000 kPa, preferably about 3400 kPa to 6800 kPa, is typically used in molding the composition. First, the mold may be coated with a release agent and prebaked.
[0070] The vulcanizate may be post-cured in an oven for about 1 hour to 24 hours or more at a temperature of about 140°C to 350°C, preferably about 200°C to 330°C, depending on the cross-sectional thickness of the sample. In the thickness section, the temperature during post-curing is usually gradually increased from the lower end of the range to the maximum desired temperature. In one embodiment, the cure temperature is greater than 300°C. In one embodiment, the cure temperature is greater than the melting point of the semi-crystalline fluoropolymer particles.
[0071] In one embodiment of the present disclosure, the composition comprising perfluorinated elastomer rubber or cured perfluorinated elastomer is essentially free of metal cations, particularly Na, K, Mg and Al cations, but also alkaline earth metal ions and alkali metal ions in general, and may contain them in amounts less than 20 ppm (parts per million), or less than 10 ppm, or even less than 1 ppm. The concentrations of alkali ions, alkaline earth ions (Na, K, Li, Mg, Ba) and Al may be less than 1 ppm individually and less than 4 ppm in total. Other ions such as Fe, Ni, Cr, Cu, Zn, Mn, Co may be less than 4 ppm in total.
[0072] A particular advantage of the method of the present disclosure is that blends of fluoroelastomers and particles can be prepared that have a low content of fluorinated emulsifier acid. Such blends can be particularly useful for applications in the semiconductor industry, since such applications not only require low metal content, but also desirably do not leak acid from the fluoropolymer article to meet the high purity requirements in semiconductor processing and manufacturing. The amorphous perfluoropolymers, semi-crystalline fluoropolymer particles, and blends thereof have very small amounts, for example, less than 2000, 1000, 500, 100, 50, 25, or even 15 ppb (parts per billion) based on the weight of the polymer, of fluorinated acids (e.g., extractable C8-C14 alkanoic acids) and salts thereof, which can be determined by extraction as described in U.S. Patent No. 2019-0185599 (Hintzer et al.), which is incorporated herein by reference. Fluorinated acids are represented by the general formula: YR f -ZM [In the formula, Y represents hydrogen, Cl or F; R f represents a divalent linear, branched or cyclic perfluorinated or partially fluorinated saturated carbon chain having 8 to 14 carbon atoms, Z is an acid group, e.g., -COO - or -SO3 - represents an acid group, and M is H + represents a cation containing the formula:
[0073] Blends comprising amorphous perfluoropolymer and particles of semi-crystalline fluoropolymer may be useful in the manufacture of seals or molds, particularly in equipment in the manufacture or purification of semiconductors or products including semiconductors, including etching equipment and vacuum evaporators. Etching equipment includes plasma etchers, reactive ion etchers, reactive ion beam etchers, sputtering etchers, and ion beam etchers.
[0074] In one embodiment, the filled perfluorinated elastomeric composition (in other words, the curable or cured composition) is translucent (i.e., allows light but no detectable features) or opaque (i.e., not transparent); such translucent or opaque materials may be achieved by using semi-crystalline fluorinated polymers having an average diameter greater than 100 nm.
[0075] In one embodiment, the cured perfluorinated elastomers of the present disclosure have exceptional properties including a melting point of 310, 315, or even 320°C or greater and up to 325, 330, 335, 340, 345, or even 350°C, a recrystallization point of less than 315, 310, 300, 280, 275, 270, 265, or even 260°C, and / or a glass transition temperature of less than 5, 0, -5, -10, -20, -30, -40, or even -50°C.
[0076] Due to the stringent requirements for the use of perfluorinated elastomers in the semiconductor industry, various test methods have been developed to predict whether a perfluorinated elastomer article is suitable for use. One such test method relates to weight loss, where a perfluorinated elastomer article is exposed to plasma and the weight loss is determined. In one embodiment, the perfluorinated elastomer of the present disclosure has a weight loss of less than 20, 10, 5, or even 1% when exposed to plasma treatment. EXAMPLES
[0077] Unless otherwise noted, all parts, percentages, ratios, etc. in the examples and the rest of the specification are by weight, and all reagents used in the examples were obtained or are available from general chemical suppliers, such as Sigma-Aldrich Company (Saint Louis, Missouri), or can be synthesized by conventional methods.
[0078] The following abbreviations are used in this section: L = liter, mg = milligram, g = gram, kg = kilogram, cm = centimeter, mm = millimeter, wt% = weight percent, min = minute, h = hour, d = day, NMR = nuclear magnetic resonance, ppm = parts per million, sccm = standard cubic centimeter, °C = degrees Celsius, mTorr = millitorr, RF = radio frequency, W = watts, and mol = mole. Abbreviations for materials used in this section, as well as a description of the materials, are provided in Table 1. [Table 1]
[0079] Fluoropolymer Particle Testing
[0080] Melting point measurement and recrystallization temperature
[0081] The preparation was allowed to solidify and dry. Melting point (T m ), glass transition temperature (T g ), and recrystallization temperature were determined on dry powders by differential scanning calorimetry (DSC Q2000, TA Instruments, New Castle, Del.) under nitrogen flow according to ASTM D 793-01 and ASTM E 1356-98. The first thermal cycle started at -85°C and was ramped to 350°C at 10°C / min. The cooling cycle started at 350°C and was cooled to -85°C at 10°C / min. The second thermal cycle started at -85°C and was ramped to 350°C at 10°C / min. DSC thermograms were obtained from the second heat of the heat / cool / heat cycle, showing T m , T g and recrystallization were determined.
[0082] particle size
[0083] The particle size determination of the latex was carried out by dynamic light scattering using a Malvern Zetasizer Nano S (Malvern, Worcestershire, UK) following a procedure similar to that described in DIN ISO 13321:2004-10. The average particle size reported is d50. Prior to the measurement, the polymer latex obtained from the polymerization was diluted with 0.01 mol / L NaCl solution. The measurement temperature in all cases was 25°C.
[0084] Tensile properties
[0085] The preparations were solidified and dried. Tests were carried out on 2 mm thick specimens for melt-processable materials and 1.6 mm thick specimens for non-melt-processable materials according to DIN EN ISO 12086-2:2006-05 and with a test speed of 50 mm / min. Tensile strength and elongation at break were determined at 23°C according to DIN EN ISO 527-1. Measurement results from 5 specimens were averaged.
[0086] Vinyl and Allyl Ether Comonomer Content
[0087] For semi-crystalline melt-processable fluoropolymer particles, thin films of about 0.1 mm thickness were prepared by molding the polymer at 350°C using a heated plate press. For semi-crystalline non-melt-processable fluoropolymer particles, thin specimens of about 0.3 mm to 0.4 mm thickness were prepared by cold compressing the polymer in a mold. These films were then scanned in a nitrogen atmosphere using an FT-IR spectrometer (Nicolet DX 510, ThermoFisher Scientific, Waltham, MA). OMNIC software (ThermoFisher Scientific) was used for data analysis. The CF2=CF-CF2-O-CF2-CF2-CF3 (MA-3) content reported herein in weight percent was determined from the 999 1 / cm infrared band and calculated as 1.24× (a factor determined by solid-state NMR) of the ratio of the absorbance at 999 1 / cm to the absorbance of the reference peak located at 2365 1 / cm. The CF2=CF-O-CF2-CF2-CF3 (PPVE-1) content, reported in weight percent, was determined from an infrared band at 993 1 / cm and calculated as 0.95x the ratio of the absorbance at 993 1 / cm to the absorbance of the reference peak located at 2365 1 / cm. The CF2=CF-O-CF3 (PMVE) content, reported in weight percent, was determined from an infrared band at 889 1 / cm and calculated as 11.2x the ratio of the absorbance at 889 1 / cm to the absorbance of the reference peak located at 2365 1 / cm. The CF2=CF-O-(CF2)5 (MV5CN) content, reported in weight percent, was determined from an infrared band at 2236 1 / cm and calculated as 2.62x the ratio of the absorbance at 2236 1 / cm to the absorbance of the reference peak located at 2365 1 / cm.
[0088] Solids
[0089] The solids content (fluoropolymer content) of the fluoropolymer particle dispersions was determined gravimetrically according to DIN EN ISO 12086-2:2006-05. No correction for non-volatile inorganic salts was made. The solids content of the polymer dispersion was taken as the polymer content.
[0090] Melt Flow Index (MFI)
[0091] For melt-processable semicrystalline fluoropolymer particles, the MFI reported in g / 10 min was measured according to DIN EN ISO 1133-1:2012-03 at a support weight of either 2.16 kg, 5.0 kg or 21.6 kg. The MFI was obtained using a standardized extrusion die with a diameter of 2.1 mm and a length of 8.0 mm. Unless otherwise stated, a temperature of 372°C was applied.
[0092] Standard specific gravity (SSG)
[0093] For non-melt processable semi-crystalline fluoropolymer particles, the preparations were coagulated and dried. The SSG of the dry powder was determined according to the protocol of DIN EN ISO 12086-2:2006-05.
[0094] Mooney Viscosity
[0095] Mooney viscosity was determined according to ISO 289-1:2015, with a 1 minute preheat and a test at 121°C for 10 minutes (ML1+10 at 121°C) using a MV2000 viscometer available from Alpha Technologies (Akron, OH, USA).
[0096] Preparation of semi-crystalline fluoropolymer particles
[0097] Preparation example A
[0098] An oxygen-free 150 L kettle was charged with 105 kg of deionized water, 2.8 kg of 30 wt% aqueous emulsifier solution, 56 g of ammonium chloride, 174 g of ammonium nonafluorobutane-1-sulfinate (as a 34 wt% solution in water) and 214 g of MV5CN pre-emulsion. The MV5CN pre-emulsion consists of 25 wt% MV5CN (CF2=CFO(CF2)5CN available from Anles, St. Peterburg, Russia), 0.4 wt% emulsifier (30 wt% aqueous solution) and 74.6 wt% water, prepared by mixing with a homogenizer. The kettle was then heated to 65°C and charged with PMVE until a pressure of 10 bar was reached, followed by TFE up to 14 bar. The polymerization was initiated by feeding 660 g of a 20 wt% aqueous solution of ammonium persulfate (APS). PMVE and TFE were constantly fed to the reactor and 7.45 kg of MV5CN pre-emulsion was added until a total of 26.3 kg of TFE had been added. After 295 minutes, a total of 24.1 kg PMVE, 28.3 kg TFE were added to terminate the polymerization. The solids content of the latex was 32.5 wt% with a d50 of 79 nm. The solid polymer showed a Mooney viscosity of 71 Mooney units and had approximately 52.4 wt% TFE, 43.7 wt% PMVE, and 3.9 wt% CF2=CFO(CF2)5CN.
[0099] Preparation Example C (Fluoropolymer Dispersion C)
[0100] A 40 L kettle was charged with 27 kg of oxygen-free deionized water, 250 g of a 30 wt% aqueous emulsifier solution, and 15 g of PPVE-2. The kettle was heated to 65°C and N2 was introduced to 5 bar, followed by TFE to 12 bar. Polymerization was initiated by feeding 6 g of ammonium persulfate (APS) (dissolved in 50 g of deionized water). After a total of 134 minutes, 9.2 kg of TFE and 20 g of PPVE-1 were fed to the reactor, the kettle was cooled to 30°C, and the pressure was released. The final latex had a solids content of 25 wt%, an average particle size (d50) of 177 nm. The latex was used for blending and was also coagulated with a 10 wt% oxalic acid solution. The dried polymer had an MFI (372°C, 21.6 kg) of 0.4 g / 10 min, an SSG of 2.195, a tensile strength of 17.6 MPa, and an elongation of 289% (measured on a sintered plate of 2 mm thickness). The PPVE-1 content in the dried polymer was 0.1 wt%. The Tm and recrystallization point of the fluoropolymer were determined as described above. Tm = 326°C and recrystallization point at 308°C.
[0101] Preparation Example D (Fluoropolymer Dispersion D)
[0102] An oxygen-free 40 L kettle was charged with 27 kg deionized water, 390 g of a 30 wt. % aqueous emulsifier solution, 100 g PPVE-1 and 200 mbar ethyl (25° C.). The reactor was heated to 75° C. and TFE was charged until a pressure of 10 bar (1 MPa) was reached. The polymerization was started by feeding 3.0 g APS (dissolved in 50 g deionized water). TFE was fed continuously at a pressure of 10 bar (1 MPa). After a total of 5.6 kg TFE, 280 g PPVE-1 was fed to the reactor and another 1 g APS was added. After 7.9 kg TFE, the polymerization was stopped. The latex had a solids content of 21 wt. % and a d50 of 122 nm. The coagulated dry polymer had a content of 0.8 wt. % PPVE-1 and an MFI of 18 g / 10 min (372° C., 5 kg). The Tm and recrystallization point of the fluoropolymer were determined as described above. Tm = 323°C and recrystallization point at 306°C.
[0103] Preparation Example E (Fluoropolymer Dispersion E)
[0104] An oxygen-free 40 L kettle was charged with 28 L of deionized water, 100 g of a 30 wt% aqueous emulsifier solution, 0.9 g of a 10 wt% aqueous tert-butanol solution, 0.9 g of oxalic acid dihydrate, and 82 g of PPVE-1. The kettle was heated to 40° C. and TFE was fed to the reactor to obtain a pressure of 15 bar (1.5 MPa). The polymerization was started by adding 70 mg of pure KMnO4 (fed as a 0.04 wt% aqueous solution) and another 70 mg of KMnO4 was added continuously throughout (133 min). After adding 7.7 kg of TFE, 50 g of pre-emulsion CF2=CF-O-(CF2)5CN in 50 g of water and 1 g of emulsifier were fed to the polymerization. After a total of 8.3 kg of TFE had been fed to the reactor, the polymerization was terminated. The latex had a solids content of 23 wt% and a d50 of 120 nm. The coagulated dry polymer had an SSG of 2.146, a PPVE content of 0.4 wt%, and a d -1 A nitrile signal was visible. The Tm of the fluoropolymer was determined as above. The Tm was 328°C with a recrystallization point at 303°C.
[0105] Preparation Example F (Fluoropolymer Dispersion F)
[0106] An oxygen-free 40 L kettle was charged with 28 kg of deionized water, 100 g of 30 wt% aqueous emulsifier solution, 7 g of 10 wt% aqueous tert-butanol solution, 0.9 g of oxalic acid dihydrate, and 50 g of MA-3 (C3F7-O-CF2-CF=CF2). The kettle was heated to 40°C and TFE was added to reach a pressure of 15 bar (1.5 MPa). Polymerization was initiated by feeding 76 mg of KMnO4 (as a 0.04 wt% aqueous solution) to the reactor. Another 40 mg of KMnO4 was added during the entire runtime (160 min). A total of 8.3 kg of TFE was added.
[0107] The final latex had a solids content of 23 wt.%, a d50 of 110 nm. The coagulated dry polymer had an SSG of 2.137 and an MA-3 content of 0.06 wt.%. The Tm and recrystallization temperature of the fluoropolymer were determined as described above. The Tm was 321°C with a recrystallization point of 306°C.
[0108] Preparation Example G (Fluoropolymer Dispersion G)
[0109] The polymer is a core-shell polymer. The material is prepared by the following procedure.
[0110] Seed latex: An oxygen-free 40 L kettle was charged with 28 kg deionized water, 150 g of a 30 wt% emulsifier aqueous solution, 1 g of oxalic acid dihydrate, 1 g of a 50 wt% solution of tert-butanol in water, and 15 g of PPVE-1. At 25°C, TFE was introduced to 15 bar (1.5 MPa) pressure. The polymerization was started with 45 mg of potassium disulfite (dissolved in 100 mL of water), followed by 0.015 g of KMnO4 (dissolved in 200 mL of water) and after 54 minutes, a total of 3.2 kg of TFE was added. The seed latex had a d50 of 85 nm and an SSG of 2.147.
[0111] 3 L of seed latex, 23 kg of deionized water, 60 g of 30 wt % emulsifier aqueous solution, 0.9 g of oxalic acid dihydrate (dissolved in 100 mL of water), 1.6 g of 10% aqueous solution of tert-butanol, and 10 g of PPVE-1 were added to a 40 L reactor. The kettle was heated to 30° C. and TFE was fed until a pressure of 14 bar (1.4 MPa) was reached. Polymerization was initiated using 50 mg of KMnO4 (dissolved in 200 mL of water). After 4 kg of TFE was fed, another 50 mg of KMnO4 was added. A total of 8 kg of TFE was added and 26 g of PPVE-1 was fed until 5 kg of TFE had polymerized. The latex had a solids content of 23 wt % and a d50 of 195 nm. The dried polymer exhibited an SSG of 2.162, a PPVE-1 content of 0.07 wt%, a tensile strength of 32 MPa, and an elongation of 385%. The Tm was 326°C, with a recrystallization point of 308°C.
[0112] Preparation Example H (Fluoropolymer Dispersion H)
[0113] The polymer is a core-shell polymer prepared by the following procedure.
[0114] Seed latex: An oxygen-free 40 L kettle was charged with 28 kg of deionized water, 300 g of 30 wt% emulsifier aqueous solution, 50 mg of potassium disulfite (in 100 mL water), 6 g of 25 wt% ammonia, 2 mg of copper(II) sulfate (in 50 mL water) and 3 g of 50 wt% tert-butanol aqueous solution. The kettle was heated to 35° C., 30 g of HFP was added and the TFE pressure was increased to 14 bar (1.4 MPa) pressure. Polymerization was initiated with 0.36 g of APS in 50 mL of water. 2.5 kg of TFE was introduced followed by 10 g of HFP. A total of 5.8 kg of TFE was transferred to the kettle. The latex had a d50 of 87 nm.
[0115] The reactor was charged with 2 L of seed latex, 26 mg of water, 150 g of a 30 wt % aqueous solution of emulsifier, 1 g of oxalic acid dihydrate, and 1.6 g of a 50% aqueous solution of tert-butanol. The kettle was heated to 42° C. and TFE was added until 14 bar (1.4 MPa). Polymerization was initiated by adding 30 mg of KMnO4 in 100 mL of water. 6.5 kg of TFE was added, followed by 5 g of HFP, followed by 5 mg of KMnO4 and TFE until a total of 7.1 kg of TFE was reached. The latex had a d50 of 190 nm, an SSG of 2.151, a tensile strength of 33.6 MPa, and an elongation of 370%. The Tm and recrystallization point of the fluoropolymer were determined as described above. The Tm was 325° C. with a recrystallization point of 313° C.
[0116] Latex Blend
[0117] Latex Blend B~H
[0118] For each of latex blends B-H, 2000 g of neat fluoropolymer dispersion A was mixed with neat semi-crystalline fluoropolymer latex in the indicated ratios, calculated on the solids content of the latex, as shown in Table 2. The mixture was coagulated by adding the blended latex dropwise, with stirring, to a solution of 3400 g deionized water and 140 g nitric acid (65%) over a period of 30 minutes. After settling the mixture, the coagulate was filtered off and washed 8 times with 8 L of deionized water. The coagulate was then dried at 115° C. under vacuum for 16 hours. The Tm was determined by DSC, and the expansion point and residual weight were determined by TGA for the dried fluoropolymer blends according to the following procedure.
[0119] Melting points of coagulated fluoropolymer blends
[0120] The melting point (T m The recrystallization point in the heat / cool scan and the recrystallization point in the cooling scan were determined by a TA Instruments Differential Scanning Calorimetry DSC Q2000 according to ASTM D 793-01 and ASTM E 1356-98 under nitrogen flow. DSC scans were obtained from -50°C to 350°C at a scan rate of 10°C / min. The first heat cycle started at -50°C and was ramped to 350°C at 10°C / min. The cooling cycle started at 350°C and was cooled to -50°C at 10°C / min. The second heat cycle started at -50°C and was ramped to 350°C at 10°C / min. DSC thermograms were obtained from the first heat of the heat / cool cycle to determine the recrystallization point and DSC thermograms were obtained from the second heat of the heat / cool / heat cycle to determine the T. m It was decided.
[0121] Inflection temperature and semi-crystalline fluoropolymer blend ratio
[0122] The inflection point temperature was determined using TGA (Thermogravimetry Analysis TGA Q500 by TA Instrument) from the derivative curve according to ASTM E 1131-08. The sample size for the test was 10.0±1 mg. The sample was heated to 650°C at 10°C / min under nitrogen flow, then further heated to 800°C at 10°C / min under air flow. The first derivative curve of the weight loss plotted against temperature showed two maxima. The temperature at which the minimum between these two maxima occurred was taken as the inflection point indicating the onset of decomposition of the semicrystalline fluoropolymer. The inflection points are shown in Table 2. The semicrystalline fluoropolymer blend ratio was determined from the weight loss curve as the ratio of the weight loss at a temperature higher than the inflection point to the total weight loss of the sample expressed as a percentage. The semicrystalline fluoropolymer blend ratio is shown in Table 2.
[0123] Extraction of perfluorinated alkanoic acids:
[0124] Surrogate recovery standard (SRS) at a concentration of 25 ppb based on the solids content of the dispersion 13 C4-PFOA( 13 After adding perfluorooctanoic acid with 4 carbon atoms substituted with C isotopes (commercially available from Campro Scientific GmbH, Berlin, Germany), the latex blend was freeze-dried to remove water. 1 g of the freeze-dried polymeric material blend was treated with 3 mL of methanol in a vial at a stirring speed of 250 rpm and a temperature of 50° C. for 16 hours to extract the perfluorinated alkanoic acids. The mixture was centrifuged (approximately 10 min at 4400 rpm) and an aliquot of the supernatant was transferred to a 2 mL autosampler vial.
[0125] The extracts were analyzed for perfluorocarboxylic acids by reversed-phase high-performance liquid chromatography (HPLC) coupled to a triple quadrupole mass spectrometer (e.g., Agilent 6460 or ABSciex API 4000 QQQ-MS) in negative multiple reaction mode (MRM) using typical transitions of the analytes, e.g., m / z 413->369 for perfluorooctanoic acid (PFOA). HPLC (Agilent 1200 or 1260) equipped with an Agilent C18 column (Zorbax Eclipse XDB-C18 4.6×50 mm 1.8 μm) was performed in gradient mode with high purity water and methanol at 50° C. Both solvents, which were LC-MS grade, were modified with 10 mmol ammonium acetate (gradient of 15% MeOH->100% MeOH). Use an equivalent or similar isotopically labeled internal standard (e.g., PFOA as an internal standard available from Campro Scientific GmbH, Berlin, Germany) with a calibration range of 0.5–200 ng / mL analyte in the methanol extract. 13 Analytes were quantified using a fluorinated C8-C8-PFOA. The resulting polymer-related lower level of quantification (LLOQ) was 1.5 ppb and the upper limit of quantification (ULOQ) was 600 ppb. Analytes with concentrations higher than the ULOQ were diluted to the calibration range with methanol and the analysis was repeated. 14 -Carboxylic acid (CF3-(CF) n The amount of -COOH; n = 6–12) was determined in this manner. [Table 2]
[0126] The blends indicated in Table 2 above containing agglomerated fluoropolymer were compounded as follows: a 6 inch (15.24 cm) two-roll mill was used to prepare 100 g of the indicated blend with 1.1 g of Catalyst A. The compounded materials were characterized by measuring the modulus, visual observation of crushed sheets, cure rheology, and compression set according to the procedures described below.
[0127] Visual inspection of compounded materials
[0128] After mixing on the mill, the blend was removed from the roll by cutting. The appearance of the resulting sheets was visually inspected. The overall visual appearance of the sheet was reported as either smooth or rough in appearance. The presence of fibrillation was determined by visually inspecting the sheet for the appearance of white lines in the sheet and was reported as absent, barely present, or present in significant amounts. The visual observations for each sample are reported in Table 3.
[0129] Compound modulus and frequency sweep
[0130] The elastic modulus at 100°C was determined using a rheometer (RPA 2000 by Alpha Technologies, Hudson, OH) at 7% strain and a frequency sweep of 0.1, 2.0 and 20 Hz from the storage modulus (G') obtained from ASTM 6204-07 Part A. The test sample size was 7.0±0.1 grams. A preconditioning step was performed prior to the elastic modulus measurement at 0.5 Hz, 62.8% strain and 100°C for 5 minutes. The results are reported in Table 3.
[0131] Cure Rheology
[0132] The cure characteristics of the compounded materials were measured using a rheometer (Rubber Process Analyzer equipped with moving die rheometer (MDR) mode, Alpha Technologies, Hudson, OH) under conditions corresponding to ASTM D5289-07. Cure rheology testing was performed on uncured compounded samples at 160°C using no preheat, 15 minute elapsed time, and 0.5 degree arc. Minimum torque (M L ), and plateau or maximum torque (M H If the torque is not available, the highest torque reached during a specific period is measured. L The time to increase by 2 units beyond t s 2) Torque is M L +0.1(M H -M L ) and the time (t'10) when the torque reaches a value equal to M L +0.5(M H -M L ) and the time (t'50) when the torque reaches a value equal to M L +0.9(M H -M L The time (t'90) to reach the critical temperature was also measured.
[0133] Compression set
[0134] O-rings (214, AMS AS568) were molded from the compounded material at 160°C for 15 minutes. The press-cured O-rings were post-cured with the following step cure sequence: the first step cure started at room temperature and was ramped to 150°C for 2 hours. It was held at 150°C for 7 hours. The second step cure started at 150°C and was ramped to 300°C for 2 hours. It was held at 325°C for 8 hours. A cooling step was then started at 325°C and cooled to room temperature for 2 hours. The post-cured O-rings were tested for compression set at 300°C and 325°C for 70 hours with an initial strain of 25% according to ASTM D 395-03 Method B and ASTM D 1414-94. Results are reported as percentages. The compression set results are summarized in Table 3. [Table 3]
[0135] Example 7
[0136] The post-cured O-rings of Example 2 were then tested using DSC to determine Tm and Tg and recrystallization following the same procedures as described above for melting point measurements and recrystallization temperatures. The second heat of the heat / cool / heat cycle showed a Tm of 321.9°C, a Tg of -3°C, and recrystallization points from the first cool of 269.3°C and 285°C.
[0137] Foreseeable modifications and variations of the present invention will be apparent to those skilled in the art without departing from the scope and spirit of the present invention. The present invention is not limited to the embodiments described in this application for illustrative purposes. In the event of any discrepancy or inconsistency between the description of this specification and the disclosure in any document mentioned in this specification or incorporated by reference, the description of this specification shall prevail. The present invention includes the following aspects. (1) A latex blend comprising an amorphous perfluoropolymer latex and an aqueous dispersion of semi-crystalline fluoropolymer particles, wherein the semi-crystalline fluoropolymer particles comprise a tetrafluoroethylene copolymer containing 1 wt. % or less of at least one additional fluorinated monomer, and the semi-crystalline fluoropolymer particles (i) have a melt flow index (at 372°C, 2.16 kg) of less than 50 g / 10 min, or (ii) are not melt processable and have a standard specific gravity of less than 2.200, and the semi-crystalline fluoropolymer particles have an average diameter of more than 100 nm. (2) The latex blend of claim 1, wherein the latex blend has a melt temperature, after coagulation and drying, of 310°C or more and up to 329°C. (3) The latex blend according to item 1 or 2, wherein the latex blend has a melt temperature, after coagulation and drying, greater than 310°C and less than 323°C. (4) The latex blend according to any one of items 1 to 3, wherein the latex blend has an inflection point temperature, after coagulation and drying, of 500°C or more and up to 510°C. (5) The latex blend according to any one of items 1 to 4, wherein the latex blend has at least one recrystallization temperature, after coagulation and drying, of less than 310° C. (6) The additional fluorinated monomer is hexafluoropropylene and a fluorinated monomer having the general formula: R f -O-(CF 2 ) m CF=CF 2 [wherein m is 0 or 1, and Rf represents a perfluoroalkyl residue containing at least one carbon atom optionally interrupted by at least one linking oxygen atom]. (7) The latex blend according to any one of items 1 to 6, wherein the semicrystalline fluoropolymer particles are core-shell particles. (8) The latex blend according to any one of items 1 to 7, wherein the latex blend comprises, based on weight, 5 wt.% or more and 50 wt.% or less of the semi-crystalline fluoropolymer particles per amorphous perfluoropolymer. (9) The latex blend according to any one of items 1 to 8, wherein the latex blend comprises, after coagulation and drying, 10% by weight or more and up to 30% by weight of said semicrystalline fluoropolymer particles. (10) The amorphous perfluoropolymer is derived from a perfluoroolefin and a perfluorovinyl ether, the perfluoroolefin being optionally selected from tetrafluoroethylene, hexafluoropropylene, or a combination thereof, and the perfluorovinyl ether being optionally selected from perfluoro(2-propoxypropyl vinyl) ether (PPVE-2), perfluoro(methyl vinyl) ether (PMVE), perfluoro(ethyl vinyl) ether (PEVE), perfluoro(3-methoxy-n-propyl vinyl) ether (MV-31), perfluoro(2-methoxy-ethyl vinyl) ether, perfluoro(n-propyl vinyl) ether (PPVE-1), perfluoro(n-propyl allyl) ether (MA-3), and F. 3 C-(CF 2 ) 2 -O-CF(CF 3 )-CF 2 -O-CF(CF 3 )-CF 2 -O-CF=CF 2 (PPVE-3). (11) The latex blend according to any one of the preceding claims, wherein the amorphous perfluoropolymer comprises cure sites selected from at least one of bromine, iodine, and nitrile. (12) The latex blend according to any one of items 1 to 11, wherein the at least one additional fluorinated monomer is a nitrile-containing perfluorinated vinyl ether. (13) The latex blend of any of the preceding claims, wherein the amorphous perfluoropolymer is substantially free of nitrile-containing cure sites. (14) The latex blend of any one of the preceding claims, wherein the latex blend composition is substantially free of metals. (15) The latex blend according to any one of items 1 to 14, wherein the semicrystalline fluoropolymer particles have a standard specific gravity of up to 2.185. (16) The latex blend according to any one of items 1 to 15, wherein the amorphous perfluoropolymer latex comprises particles of amorphous perfluoropolymer having an average particle size of 50 nm or more up to 200 nm. (17) The latex blend according to any of the preceding claims, wherein the latex blend contains, after coagulation and drying, less than 1000 ppb of a C8-C14 fluorinated emulsifier, based on the weight of the fluoropolymer. (18) A method for producing a homogeneous perfluoropolymer blend, comprising the steps of: blending an amorphous perfluoropolymer latex with an aqueous dispersion of semi-crystalline fluoropolymer particles, the semi-crystalline fluoropolymer particles comprising a tetrafluoroethylene copolymer containing 1 wt. % or less of at least one additional fluorinated monomer, the semi-crystalline fluoropolymer particles either (i) having a melt flow index (at 372° C., 2.16 kg) of less than 50 g / 10 min, or (ii) being not melt processable and having a standard specific gravity of less than 2.200, the semi-crystalline fluoropolymer particles having an average diameter of greater than 100 nm; and solidifying said blend. 19. The method of claim 18, wherein the solidification step comprises the steps of acid, high shear, freezing, and / or ceramic and / or glass particles. (20) A polymer blend obtained by the method according to item 18 or 19. (21) The polymer blend according to item 20, wherein the polymer blend has a melting temperature greater than 310°C and less than 325°C. (22) The polymer blend according to item 20 or 21, wherein the polymer blend has an inflection point temperature of 500°C or more and up to 510°C. (23) The polymer blend according to any one of items 20 to 22, wherein the polymer blend has at least one recrystallization temperature of less than 310° C. (24) The polymer blend according to any one of items 20 to 23, wherein the polymer blend has an elastic modulus of less than 450 KPa at a frequency of 0.1 Hertz and 100° C. (25) The polymer blend according to any one of items 20 to 24, wherein the polymer blend has a ML of less than 2.9 dNm. (26) A curable perfluoropolymer composition comprising a homogeneous blend of (i) an amorphous perfluoropolymer latex and (ii) an aqueous dispersion of semi-crystalline fluoropolymer particles, the semi-crystalline fluoropolymer particles comprising a TFE copolymer containing 1 wt.% or less of at least one additional fluorinated monomer, the semi-crystalline fluoropolymer particles either (a) having a melt flow index (at 372°C, 2.16 kg) of less than 50 g / 10 min, or (b) not being melt processable and having a standard specific gravity of less than 2.200, and the semi-crystalline fluoropolymer particles having an average diameter of more than 100 nm. (27) A cured perfluorinated elastomer comprising a perfluoropolymer filled with semicrystalline fluoropolymer particles, the semicrystalline fluoropolymer particles comprising a tetrafluoroethylene copolymer containing 1 wt. % or less of a second fluorinated monomer, the semicrystalline fluoropolymer particles either (i) having a melt flow index (at 372° C., 2.16 kg) of less than 50 g / 10 min, or (ii) not melt processable and having a standard specific gravity of less than 2.200, the semicrystalline fluoropolymer particles having an average diameter of more than 100 nm. (28) A cured perfluorinated elastomer filled with semicrystalline fluoropolymer particles, the semicrystalline fluoropolymer particles comprising a tetrafluoroethylene copolymer containing 1 wt. % or less of a second fluorinated monomer, the semicrystalline fluoropolymer particles either (i) having a melt flow index (at 372°C, 2.16 kg) of less than 50 g / 10 min, or (ii) being not melt processable and having a standard specific gravity of less than 2.200, the filled cured perfluorinated elastomer having a melting point of 310°C to 350°C, and a recrystallization point of less than 300°C. (29) A method for producing a fluoroelastomer article, comprising: providing a latex blend according to any one of items 1 to 17; coagulating the latex to form a solid blend; molding the solid blend; and curing the molded solid blend to form the fluoroelastomer article. 30. The method of claim 29, wherein the curing is carried out at a temperature greater than 300°C. (31) The method according to item 30, wherein the curing is carried out by heating the shaped solid blend to a temperature above the melting point of the semi-crystalline fluoropolymer particles.
Claims
1. A latex blend comprising an amorphous perfluoropolymer latex and an aqueous dispersion of semi-crystalline fluoropolymer particles, said latex blend comprising, by weight, 5% by weight or more and 50% by weight or less of said semi-crystalline fluoropolymer particles per said amorphous perfluoropolymer; The semi-crystalline fluoropolymer particles comprise a tetrafluoroethylene copolymer derived from tetrafluoroethylene and at least one additional fluorinated monomer, the tetrafluoroethylene copolymer comprising from 0.01% to 1% by weight of the at least one additional fluorinated monomer, the additional fluorinated monomer being a perfluorovinyl or allyl ether monomer; The semi-crystalline fluoropolymer particles (i) have a melt flow index (at 372° C., 2.16 kg) of less than 50 g / 10 min; or (ii) are not melt processable and have a melt flow index (at 372° C., 2.16 kg) of less than 0.1 g / 10 min and a standard specific gravity of less than 2.200; The semi-crystalline fluoropolymer particles have a melting point of 310° C. or more; The semi-crystalline fluoropolymer particles have an average diameter of greater than 100 nm; The latex blend contains, after coagulation and drying, less than 500 ppb of extractable C8 to C14 fluorinated alkanoic acids.
2. 10. The latex blend of claim 1, wherein the latex blend has a melting point of greater than or equal to 310°C and up to 329°C after coagulation and drying.
3. 3. The latex blend of claim 1 or 2, wherein the latex blend has an inflection point temperature after coagulation and drying of greater than or equal to 500°C and up to 510°C.
4. The latex blend of any one of claims 1 to 3, wherein the latex blend has at least one recrystallization temperature after coagulation and drying of less than 310°C.
5. The additional fluorinated monomer has the general formula: R f -O-(CF 2 ) m CF=CF 2 wherein m is 0 or 1 and Rf represents a perfluoroalkyl residue containing at least one carbon atom optionally interrupted by at least one catenated oxygen atom.
6. The latex blend of any one of claims 1 to 5, wherein the semi-crystalline fluoropolymer particles are core-shell particles.
7. The latex blend of any one of claims 1 to 6, wherein said semi-crystalline fluoropolymer particles have a standard specific gravity of up to 2.
185.
8. 8. The latex blend of any one of claims 1 to 7, wherein the amorphous perfluoropolymer latex comprises particles of amorphous perfluoropolymer having an average particle size of from 50 nm or more up to 200 nm.
9. 1. A method for producing a homogenous perfluoropolymer blend, comprising: Blending an amorphous perfluoropolymer latex with an aqueous dispersion of semi-crystalline fluoropolymer particles, the amount of said semi-crystalline fluoropolymer particles is, based on weight, 5% by weight or more and 50% by weight or less per said amorphous perfluoropolymer; blending said semi-crystalline fluoropolymer particles comprising a tetrafluoroethylene copolymer derived from tetrafluoroethylene and at least one additional fluorinated monomer, comprising from 0.01% to 1% by weight of at least one additional fluorinated monomer, said additional fluorinated monomer being a perfluorovinyl or allyl ether monomer, said semi-crystalline fluoropolymer particles (i) having a melt flow index (at 372°C, 2.16 kg) of less than 50 g / 10 min, or (ii) not melt processable, having a melt flow index (at 372°C, 2.16 kg) of less than 0.1 g / 10 min, and having a standard specific gravity of less than 2.200, said semi-crystalline fluoropolymer particles having an average diameter of more than 100 nm, said semi-crystalline fluoropolymer particles having a melting point of 310°C or greater; and solidifying the blend. The method wherein the blend, after agglomeration and drying, contains less than 500 ppb of extractable C8 to C14 fluorinated alkanoic acids.
10. 1. A cured perfluorinated elastomer comprising semi-crystalline fluoropolymer particles dispersed in a perfluoropolymer, the amount of said semi-crystalline fluoropolymer particles is, based on weight, 5% by weight or more and 50% by weight or less per said perfluoropolymer; the semi-crystalline fluoropolymer particles comprise a tetrafluoroethylene copolymer derived from tetrafluoroethylene and at least one additional fluorinated monomer, the tetrafluoroethylene copolymer comprising up to 1 wt.% of a second fluorinated monomer, the additional fluorinated monomer being a perfluorovinyl or allyl ether monomer; The semi-crystalline fluoropolymer particles (i) have a melt flow index (at 372° C., 2.16 kg) of less than 50 g / 10 min; or (ii) are not melt processable and have a melt flow index (at 372° C., 2.16 kg) of less than 0.1 g / 10 min and a standard specific gravity of less than 2.200; The semi-crystalline fluoropolymer particles have an average diameter of greater than 100 nm; The semi-crystalline fluoropolymer particles have a melting point of 310° C. or more; The cured perfluorinated elastomer contains less than 500 ppb extractable C8 to C14 fluorinated alkanoic acids.
11. Semi-crystalline fluoropolymer particles dispersed in a cured perfluorinated elastomer, comprising: the amount of said semi-crystalline fluoropolymer particles is, based on weight, 5% by weight or more and 50% by weight or less per said total fluorinated elastomer; the semi-crystalline fluoropolymer particles comprise a tetrafluoroethylene copolymer derived from tetrafluoroethylene and at least one additional fluorinated monomer, the tetrafluoroethylene copolymer comprising up to 1 wt. % of a second fluorinated monomer, the additional fluorinated monomer being a perfluorovinyl or allyl ether monomer; The semi-crystalline fluoropolymer particles (i) have a melt flow index (at 372° C., 2.16 kg) of less than 50 g / 10 min; or (ii) are not melt processable and have a melt flow index (at 372° C., 2.16 kg) of less than 0.1 g / 10 min and a standard specific gravity of less than 2.200; The semi-crystalline fluoropolymer particles have a melting point of 310° C. or more; Semi-crystalline fluoropolymer particles, wherein the blend of said semi-crystalline fluoropolymer particles and said cured perfluorinated elastomer has a melting point of from 310° C. to 350° C., a recrystallization point of less than 300° C., and contains less than 500 ppb of extractable C8-C14 fluorinated alkanoic acids.
Citation Information
Patent Citations
Fluoroelastomer composition
JP2000239470A
Fluoroelastomer composition
JP2002356597A
vulcanizable fluoroelastomer composition
JP2011504531A